Analisis SWOT Potensi dan Daya Tarik Wisata Osing Kemiren Dalam Rangka Pengembangan Desa Adat Osing Kemiren Kecamatan Glagah Kabupaten Banyuwangi Tahun 2021 - Lestari, Luluk; Tripalupi, Lulup Endah (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This research is a qualitative descriptive study, which is aims to analyze how tourism development in the Osing Kemiren Traditional Village using a SWOT analysis (Strength, Weakness, Opportunity and Treats). This research shows that the strength of the tourism object in the Osing Kemiren Traditional Village has the potential for a panoramic view of the village which is still beautiful, the availability of interesting events, cleanliness, good facilities and infrastructure and community friendliness. The weaknesses of the Osing Kemiren Traditional Village, the lack of clean water available in the toilets, the lack of a security and supervision system, and low human resources. Opportunities for the Osing Kemiren Traditional Village, cultural preservation of the surrounding community, opening jobs, government policies, availability of information on tourism objects on the internet and social media. The threat of the Osing Kemiren Traditional Village, the number of competitors and the development of competitor tourism facilities. From the SWOT diagram, it can be seen that the research results show that the intersection point (2.38: 2.37) is in diagram I. So, the right strategy to be applied in the tourism development strategy of the Osing Kemiren Traditional Village is to support the policy (Growth Oriented Strategy).